The Evolution of China’s Food Coupons from the Rise to the Exit of the Historical Stage - Xiao, Dingjia (International Journal of Global Economics and Management, 2024)
After the founding of New China, the food shortage situation remained severe. To ensure the production and supply of grain, food stamps were issued, which kicked off the use of food stamps in the era of planned economy. In developing and evolving, the controlled procurement and distribution system and the food coupon system once faced a crisis when the relationship between the state and farmers showed an “imbalance” anomaly. In this connection, the state made multiple adjustments to the controlled procurement and distribution policy, with an approach focusing on resolving the crisis while adhering to the controlled procurement and distribution system as the main direction of reform.